PELATIHAN INTEGRASI DATABASE DAN AUTOMASI DATA MENGGUNAKAN N8N UNTUK OPTIMALISASI SISTEM INFORMASI - Khaerul Anam; Dian Ade Kurnia; Muhammad Burhanudin; Johana Darmawan (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The community service activity with the theme "Database Integration and Data Automation Training Using n8n for Information System Optimization" was carried out as an effort to improve the digital competence of vocational high school students and educators in Cirebon Regency in facing the needs of digital transformation. The activity was carried out on April 11, 2026 through workshops, demonstrations, and direct practice using the n8n platform. This program was motivated by the fact that many schools still manage academic data manually using separate spreadsheets, resulting in inefficient data processing, potentially leading to data duplication, and complicating the monitoring and reporting process. In addition, participants' understanding of database integration and workflow automation was still relatively limited. The training material covered basic concepts of information systems, database integration, utilization of APIs and webhooks, and implementation of workflow automation using the n8n platform. Participants gained hands-on experience in building simple workflows, such as integrating Google Sheets with Telegram, synchronizing digital form data, and automating notification delivery. The activity was attended by participants from SMK Presiden Cirebon, SMKN 1 Kedawung, SMK Islamic Center Cirebon, SMK Muhammadiyah Cirebon, SMK Wahidin Cirebon City, and SMK Budi Tresna Cirebon Regency. The results of the activity showed an increase in participants' understanding and skills in applying data integration technology and information system automation. Participants successfully developed various simple automation workflows that can be implemented to support the effectiveness of academic administration in schools. The evaluation of the activity showed that the level of participant satisfaction was in the very good category. In general, this activity succeeded in making a positive contribution to increasing digital literacy, strengthening information technology competencies, and developing the use of n8n-based automation workflows in vocational education environments.